TECHNOGENIC GROUNDWATER FLOWS, THEIR ROUTING AND CREATING ROUTES ARTIFICIAL GEOCHEMICAL BARRIERS - Polevich, O.; Chuenko, O.; Udalov, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Anthropogenic groundwater flows are a worldwide problem being the source and distribution of many harmful and toxic elements entering the environment. Anthropogenic groundwater flows are included in hypergenic cycles of migration, significantly changing not only hydrochemical type of groundwater and other natural waters, but also landscapes. Actual environmental problem is the timely migration paths of pollutants and chemical elements tracking in anthropogenic groundwater flows. This allows us to identify the most contaminated areas and to take appropriate protective measures. Purpose. Development of algorithm to identify movement paths of anthropogenic groundwater from the feed zone to the discharge zone and the methodology of creating on their way the artificial geochemical barriers for preventing the spread of heavy metals. Methods. Identification of ways in which anthropogenic groundwater is carried out according to the method spray test with the launch and registration of the indicators in the streams. Indicators checking (determination of the content of heavy metals in groundwater) is carried out by xray fluorescence analysis on a multi-channel spectrometer SRM-25. Findings. The paper presents general principles, development and implemention of an algorithm for identifying motion paths of anthropogenic groundwater from the pollution source to the area of discharge. The method of creating artificial geochemical barriers on the basis of oxalic-aluminosilicate gels on the way of anthropogenic groundwater flow was developed and tested. It will reduce the concentration of harmful elements in these streams and prevent the spread of these elements from getting into soils and potable groundwater. Scientific novelty. The developed algorithm to identify movement paths of flows of anthropogenic groundwater allows to solve the inverse problem – identification of pollution sources of the studied objects located in the area of discharge of these streams. The advanced techniques of x-ray fluorescence analysis, which significantly improve its metrological performance, will be useful for rapid and cheap determination of the elemental composition of the samples of environmental objects and for studies of spatial and temporal distribution of elements almost in real time. Practical significance. The studies and their results have provided us with new information about the behavior of heavy metals in the paths of anthropogenic ground waters motion and their influence on the ecological condition of neighboring landscapes. The developed procedures to identify movement paths of anthropogenic flows of groundwater and monitoring the dynamics of these flows allow, in urgent cases, to create a special rudimentary barriers to block the distribution of heavy metals, giving the opportunity to adjust environmental and water protection measures.